The Role of “Warm-glow Giving” in Mitigating Climate Change and Promoting Sustainable Economic Growth - Gomez-Cuenca, Carolina (2022)
This dissertation studies how the incentives behind the new direction of the international climate change negotiations since 2015 can be modelled by combining the two theories of warm-glow giving and endogenous growth. Linking these two theories in this context for the first time confirms that a country's environmental commitments and economic growth are not mutually exclusive. This dissertation provides a framework on which future International Environmental Agreements (IEAs) can be based in order to avoid an environmental disaster.